Ajrak Beyond Borders: Revival and Reinvention of a South Asian Textile Heritage in Europe - Malik, Omair Javaid (International Journal of Research in Interdisciplinary Studies, 2026)
Ajrak is recognised as a centuries-old block-printed textile tradition from the Indus Valley, representing identity and artistic sustainability, but this article analyses the revival and reinvention of this traditional textile for modern global audiences via experimental design techniques that combine traditional craft with modern technologies. The primary aim of this article is to reposition Ajrak in the sustainable European fashion market; therefore, it explores the development of a prototype winter outerwear line with three-dimensional interpretations of classic patterns supported by 3D printing techniques, adding visual appeal to Ajrak patterns while retaining its traditional integrity. The findings of this article demonstrate that surface design innovation effectively creates new sensory experiences that improve the user-garment relationship and historical appreciation in modern fashion, while this reinvention also meets the European need for sustainable and meaningful fashion by revitalizing traditional craft through adaptable design. The article concludes with the prospect and potential of fusion between the traditional garment product of Ajrak with contemporary technologies to preserve cultural memory, allowing transnational revival and reinvention of Ajrak as a global fashion design language.